Досвiд використання супутникових даних для оцiнки стану грунтiв з метою розв’язання природоресурсних задач - Сахацький, О.І. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper presents the background and the results of investigations of the soil type and the humus content in soil using satellite data from Landsat-7 ETM+ and AVHRR/NOAA. The experimental evaluation of the humus content within two test sites within the Chernigovska and Khmelnitska oblasts of Ukraine is carried out. The results of humus evaluations are well correlated (coefficient of determination r2 6 0.92) with remote sensing data. The proposed approach will be useful for the solution of the problems of agriculture, natural resources, and protection of the environment.